PENGARUH PENGETAHUAN PRODUK, KEPERCAYAAN, PERSEPSI HARGA, DAN RISIKO YANG DIMILIKI TERHADAP MINAT BELI PRODUK TONGSIS “TONGKAT NARSIS” DI PAMERAN GADGET JOGJA EXPO CENTER (JEC) - Atika Putri Kinanthi (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2015)
The purpose of this study was to describe product knowledge, trust, perceived price and perceived risk on the purchasing intention of Tongsis “Tongkat Narsis” in gadget exhibition Jogja Expo Center (JEC). This study classified as a insidental sampling reseach. Thew population is 100. Data collection using a questionnaire, while data analysis techniques using multiple regression analysis by T-Test, and the classical assumption test of normality test, heteroscedasticity and multicollinearity test. The result showed the multiple linear regression model is Y= -0,227XI+0,084X2+0,212X3-0,071X4+e. That is, product knowledge (X1), Trust (X2), Perceived price (X3), and perceived risk (X4) ontributes greatly to the purchasing intention. The magnitude of the effect seen from the detemination coefficient (. Value of the determinant coefficient (. The result show that the coefficient determinant of product knowledge, Trust, Perceived Price and Perceived Risk have a positif influence on purchasing intention by 6,32% and the remaining 93,7% is influenced by other factors. Keywords: product knowledge, Trust, Perceived Price, Perceived Risk and Purchasing Intention.